Pengendalian Kualitas Produk Polyester Staple Fibre Menggunakan Metode Six Sigma di PT XYZ - Wulandari, Riska; Nurul Azizah, Fahriza (UNISTEK, 2024)
This research aims to improve the quality control of polyester staple fiber products produced by PT XYZ. The goal is to minimize downgrades on products during a specific period. The method used is the six sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. In the define stage, four Critical To Quality (CTQ) factors were identified, with Fused Fiber (FF) being the most significant at 28.9%. The measure stage yielded a Defect Per Million Opportunities (DPMO) value of 6346.1 and a sigma level of 4. The analyze stage utilized a fishbone diagram to identify the causes of issues in the human, material, method, machine, and environment aspects of each CTQ. The improve stage applied the 5W + 1H method, which is an extension of the fishbone diagram. Lastly, the control stage involves the supervision of improvement recommendations. By implementing these steps, the research aims to enhance the quality of polyester staple fiber products and minimize the impact of downgraded products on the company's goals and profitability.